Determinants and impacts of digital library usage: a survey among selected Iranian universities / Ismail Samadi - Samadi, Ismail (2016)
In the age of information, digital library (DL) adoption among Iranian universities and academic higher learning institutions has been very common. It is no longer considered as a lavish technological investment, but rather treated as technological need and necessity crucial to the survival of the university. Various studies have revealed that universities and academic higher learning institutions have benefitted from the installation of the digital libraries. In an academic environment, DL usage is purely volitional or optional. Innovative users would effectively use the DL for some specific reasons and objectives, while others may simply ignore it. This situation simply suggests that there are some determining factors that shape the usage behavior of the users. Given that digital libraries (DL) have been implemented in most Iranian universities and academic higher learning institutions, knowledge regarding users’ usage behavior is still very limited.